The Influence of Self-awareness, Digital Competence and Self-efficacy on Professionalism - Agus Ngurah Maha Krisna; Hapzi Ali (Dinasti International Journal of Digital Business Management, 2026)
The Influence of Self-Awareness, Digital Competence, and Self-Efficacy on Professionalism is a scientific article of literature study in the scope of the field of human resource management science. The aim of this article is to develop a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. Research method with library research sourced from e-books and open access e-journals. Analysis using qualitative descriptive. The results of this article: 1) Self-awareness influences Professionalism; 2) Digital Competence influences Professionalism; and 3) Self-efficacy influences Professionalism